Alcohol-Preferring Rats Show Goal Oriented Behaviour to Food Incentives but Are Neither Sign-Trackers Nor Impulsive. - Yolanda Peña-Oliver; Chiara Giuliano; Daina Economidou; Charles R Goodlett; Trevor W Robbins; Jeffrey W Dalley; Barry J Everitt (PLoS ONE)
Drug addiction is often associated with impulsivity and altered behavioural responses to both primary and conditioned rewards. Here we investigated whether selectively bred alcohol-preferring (P) and alcohol-nonpreferring (NP) rats show differential levels of impulsivity and conditioned behavioural responses to food incentives. P and NP rats were assessed for impulsivity in the 5-choice serial reaction time task (5-CSRTT), a widely used translational task in humans and other animals, as well as Pavlovian conditioned approach to measure sign- and goal-tracking behaviour. Drug-naïve P and NP rats showed similar levels of impulsivity on the 5-CSRTT, assessed by the number of premature, anticipatory responses, even when the waiting interval to respond was increased. However, unlike NP rats, P rats were faster to enter the food magazine and spent more time in this area. In addition, P rats showed higher levels of goal-tracking responses than NP rats, as measured by the number of magazine nose-pokes during the presentation of a food conditioned stimulus. By contrast, NP showed higher levels of sign-tracking behaviour than P rats. Following a 4-week exposure to intermittent alcohol we confirmed that P rats had a marked preference for, and consumed more alcohol than, NP rats, but were not more impulsive when re-tested in the 5-CSRTT. These findings indicate that high alcohol preferring and drinking P rats are neither intrinsically impulsive nor do they exhibit impulsivity after exposure to alcohol. However, P rats do show increased goal-directed behaviour to food incentives and this may be associated with their strong preference for alcohol.